Pengaruh Model Pembelajaran Problem Posing Terhadap Kemampuan Berpikir Intelektual Anak Pada Mata Pelajaran IPA Kelas VI MIS Al-Huda Langkat - Husnah, Diah Hafizhotul; Syahfitri, Diani; Nisa, Khairatun (LPPPI Publishing, 2024)
This study aims to study the effect of Problem Posing learning model on students' intellectual thinking ability in science subjects at MIS Al-Huda. This study used a quantitative approach with experimental methods, the subjects of this study were grade VI students of MIS Al-Huda totaling 21 people who were divided into two groups, namely the experimental group who received learning with the Problem Posing model and the control group who received conventional learning. The research instrument was an intellectual thinking ability test adapted from the standard of critical and creative thinking skills. Data were analyzed using inferential statistical analysis techniques with inferential t-test. The results showed that there was a significant difference between the intellectual thinking ability scores of students taught with the Problem Posing model compared to students taught with the conventional model. Students in the experimental group showed higher improvement in analysis, synthesis, and evaluation thinking ability. This objective indicates that the Problem Posing learning model is effective in improving students' intellectual thinking skills in science subjects in class VI of MIS Al- Huda, Hinai, Langkat District.